HIV voluntary testing among portuguese women attending family planning clinics: mplications for HIV prevention education and testing - Cunha Veiga Costa, Eleonora (2015)
The aim of this article is to analyze the factors associated with HIV testing among 767 sexually active women. Participants were administered several self-report questionnaires that assessed behavioral and psychosocial measures. Overall, 59.8% of the participants reported ever having tested for HIV. Results show that higher levels of education, being pregnant or having been pregnant, concern about AIDS, AIDS knowledge, self-efficacy in condom negotiation and perception of no risk in partner significantly predicted the likelihood of testing among women. Attending the mass was negatively associated with HIV testing. These findings provide information that can be used in the development of a focused gender sensitive HIV prevention program to increase HIV testing.